1993
DOI: 10.1073/pnas.90.6.2340
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of anti-human immunodeficiency virus (HIV) antibody production in HIV-1-infected infants.

Abstract: The early serologic response of infants to infection with human immunodeficiency virus type 1 (HIV-1) is normally obscured by the presence of transplacentally acquired maternal HIV antibody. By measuring HIV antibody produced in vitro by lymphocytes isolated from peripheral blood of infants and children of HIV-1-infected mothers, we have been able to study the natural acquisition of humoral immunity to perinatal HIV-1 infection. One hundred ninety-seven infants of HIV-1-infected women were studied prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…This rapid disease progression and mortality is also seen in newborn macaques inoculated with SIV/Delta B670 (3), and the disease resembles that which is seen in a small percentage of SIV-inoculated adolescent and adult macaques that fail to mount a strong immune response (15). Persistent viremia and weak antiviral immune responses are also seen in perinatally infected children who show rapid disease progression (1,4,9,10,30,35,36).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This rapid disease progression and mortality is also seen in newborn macaques inoculated with SIV/Delta B670 (3), and the disease resembles that which is seen in a small percentage of SIV-inoculated adolescent and adult macaques that fail to mount a strong immune response (15). Persistent viremia and weak antiviral immune responses are also seen in perinatally infected children who show rapid disease progression (1,4,9,10,30,35,36).…”
Section: Resultsmentioning
confidence: 84%
“…However, starting AZT administration early in infection may produce greater beneficial effects than waiting until symptomatic disease becomes apparent, especially for infants, who may show rapid disease progression. Because the rapid development of AIDS in these infants is associated with high levels of viremia and weak antiviral immune responses (4,9,30,35), one would predict that AZT administration during the early stages of HIV infection may alter the natural history of infection by reducing the initial viremia which is responsible for early systemic dissemination.…”
mentioning
confidence: 99%
“…As newborns are unlikely to have this pool of memory B cells, it is possible that the specificity of the early antibody response to HIV infection differs between adults and infants. Because the presence of maternally acquired antibodies clouds the investigation of infant antibody responses, Pollack et al (44) assessed the ability of lymphocytes isolated from 46 HIV-infected infants age 0 to 12 months to produce HIV-specific antibodies in vitro. Their results indicated that in the neonatal period, infants produced only low levels of antibodies against a restricted number of HIV antigens, but by 6 months of age, the majority of infants had detectable levels of antibodies against two or more HIV antigens.…”
Section: Immune Responses To Hiv Infection In Infants and Adultsmentioning
confidence: 99%
“…has been to infectious virus with consequent elimination of the infection is unknown (6)(7)(8)(9)(10)(11)(12). Further to this point, a welldocumented instance of the apparent clearing of neonatal HIV infection has been reported (13).…”
mentioning
confidence: 99%